Customer Intimacy in Mobile Retail - Míček, Martin; Halík, Jaroslav, 1961-; Malý, Josef, 1958-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The master thesis deals with the topic of customer intimacy in mobile telecommunications and describes how the concept of a value-based strategic approach called "customer intimacy" can be applied in telecommunications industry, illustrated on an example of a mobile operator customer relationship lifecycle model. The goal of the thesis is to evaluate mobile telecommunications industry potential for application of the value discipline of customer intimacy and illustrate a high-level framework of Customer Lifecycle Management model as the first transformational step towards customer-intimate organizational design. The thesis sets main hypothesis on the assumption that adoption of the strategy and principles of customer intimacy enable a mobile operator to capture ownership of positive customer experience and secure a sustainable competitive advantage, thereby presenting a powerful counter-measure against the zero-growth industry outlook. As a sub-hypothesis the author postulates the statement that CLM infuses highly-effective methods to capture additional customer value and positively affect mobile operators' profitability. The theoretical part defines characteristics and components of customer value in business relationships and describes truths featuring the new world of competition. This new paradigm of competition leads to the definition of rules for delivering superior value in the following subchapter. Consequently, three value-based strategic approaches towards market leadership (denoted as "value disciplines") are identified and characterized. The second part presents the goals and key principles of the value discipline of customer intimacy and adverts to distinctions in theory and business practice. The author identifies forces driving strategic initiatives focusing on customer value perception and expectations. In this part the opportunities for adoption of customer intimacy in consumer telecommunications industry are also assesses.
The penultimate subchapter describes concept of customer experience cycle that will be leveraged in the practical part of the thesis. The last subchapter then examines the importance of service identity for telecoms' successful adoption of the discipline of customer intimacy. The third part is analytical and provides industry research of European telecommunications market. The individual subchapters describe trends in development of fundamental performance indicators. In the fourth, practical part, the author presents the topic of customer lifecycle management. It describes what basic set of expectation customers have towards the relationship with a mobile operator. Then, a conceptual framework of customer lifecycle model is composed and analyzed. The penultimate subchapter pinpoints measures of value based customer profitability, interprets their applicability for decision-making on market investments, and indicates their interlock to value for shareholders. In the last subchapter, a set of recommendations is provided to mobile operators considering infusion of customer intimate principles into their organization. With respect to the practical part and main hypothesis, the author regards the goal of the thesis as fully achieved and the sub-hypothesis of the practical part as confirmed as well. The author used the following methods of research: general research of corporate strategy, marketing and CRM literature, interviews with telecommunications professionals, analysis of corporate financial filings, collection and reading of market research papers and consulting reports, study of statistical data.
Vedoucí práce: Jaroslav Halík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses